Effects of the Herbicide Atrazine on Crustacean Reproduction. Mini-Review - Silveyra, Gabriela R.; Medesani, Daniel A.; Rodríguez, Enrique M. (Frontiers in Physiology, 2022)
Atrazine, one of the most intensively applied herbicides worldwide, is commonly found in several water bodies, affecting the associated fauna. Authochon crustacean species have been relatively less studied, compared to vertebrate species, particularly concerning reproductive success. In this review, we summarize the relevant information about the effect of atrazine on the main reproductive aspects of crustaceans. One of these is related to the inhibition of ovarian growth. In this respect, a diminished vitellogenin content was found in the ovary of crabs exposed to atrazine during the entire period of ovarian growth, in correlation with a reduced oocyte size and a delay of ovarian maturation. Similar results were observed in crayfish. Atrazine was also able to affect the reproductive process, acting as an endocrine disrupter. In this sense, this herbicide was suspected to affect the secretion of some neurohormones involved in the gonadal growth, as well as to alter the circulating levels of steroid hormones which promote the synthesis of vitellogenin for ovarian growth. Moreover, atrazine produced in juvenile crayfish a sexual differentiation with a higher proportion of females, while an increment of male production was observed in daphnids. Another aspect affected by this herbicide was the reduction of offspring production, as well as several embryonic abnormalities; genotoxic effects have been also reported in crayfish. Finally, some metabolic imbalances, such as reduction in energy reserves, have been observed in some species, together with oxidative stress and histopathological effects